Otimização do rendimento do conversor DAB aplicado ao transformador eletrônico - Piveta, Renan (2015)
This work developed a deep investigation about different three level three level modulation patterns that the DAB converter can operate, and the impact of these different patterns over the converter power flow and efficiency. The DAB converter can be controlled by three design variables, here defined as control trio (D1, D2, φ). D1 is the duty cycle applied to the high voltage Full Bridge, D2 is the duty cycle applied to the low voltage Full Bridge and φ is the angle between the voltages. For the selection of the control trio that allow the current flow reduction and the efficiency maximization, two algorithms based on the sweep of these variables have been developed. First, the switching frequency (fs), the transformation ratio (a) and the inductance (LHV) are defined by the weighted average efficiency (standards) which result in an optimum design (maximum efficiency) considering the transformer load curve. On the second algorithm, one figure of merit is used, here called current factor , which finds the control trio to mitigate the power flow for each operation point, specified by input and output voltages and power. As result, this work figures out the best relation of design parameters (fs, a, LHV) and of the control trio (D1, D2, φ) for all the operation range (power and voltages variations in a defined period) that results in a maximum efficiency to the DAB converter, according with the component technologies. An analysis of the conditions to get zero voltage switching on semiconductors is also performed.